Saline springs in the Andean Region: Findings from the Microbiology - Díaz, Carolina; Rubiano, Carolina; Baena, Sandra (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2009)
The aim of this study was to identify the composition of the microbial iversity on three terrestrial saline springs in colombian Andes (Departments of Risaralda and Boyacá). For the accomplishment of this work two located saline springs in Central Mountain range (Salado de Consotá and Salado La Cristalina) and one located in the Eastern Mountain range were selected (Salpa). The saline spring Salado de Consotá is characterized by its archaeological findings, their high salinity, pH neutral oscillating between 6,7 and 7,4, and high values of calcium, chlorides and sulphates. Whereas the spring La Cristalina one (Arabia) has pH alkaline near 8,5, a contained calcium minor, but also high values of sulphates and chlorides. The saline spring Salpa, whose chemical composition is characterized by the high sulphate concentration is used at the moment for the commercial production of Na SO . 2 4 The obtained results show that these habitat are highly diverse and that still it is left much to know on his diversity, nevertheless, is evident that the microbial composition is dominated by organisms of the class alpha and gamma proteobacteria.